2000
DOI: 10.1038/labinvest.3780180
|View full text |Cite
|
Sign up to set email alerts
|

K15 Expression Implies Lateral Differentiation within Stratified Epithelial Basal Cells

Abstract: SUMMARY:Keratins are intermediate filament proteins whose expression in epithelial tissues is closely linked to their differentiated state. The greatest complexity of this expression is seen in the epidermis and associated structures. The critical basal (proliferative) cell layer expresses the major keratin pair, K5 and K14, but it also expresses an additional type I keratin, K15, about which far less is known. We have compared the expression of K15 with K14 in normal, pathological, and tissue culture contexts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
71
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(82 citation statements)
references
References 39 publications
9
71
0
2
Order By: Relevance
“…As indicated earlier, some caution is required in use of K15 as a putative stem cell marker, since its expression patterns in various normal and pathological situations has not been exhaustively investigated, in spite of the fact that it was identified in 1982 [12,30]. We therefore used K15-specific antibodies and first confirmed K15 localization in relation to another well-established developmental stagespecific keratin, K14, which delineates undifferentiated epidermal basal cells in stratified epithelia [13,26,31], in various epithelia of newborn CD1 wild type mice, including the oral epithelium ( Fig. 1a and b), tongue ( Fig.…”
Section: Resultsmentioning
confidence: 76%
“…As indicated earlier, some caution is required in use of K15 as a putative stem cell marker, since its expression patterns in various normal and pathological situations has not been exhaustively investigated, in spite of the fact that it was identified in 1982 [12,30]. We therefore used K15-specific antibodies and first confirmed K15 localization in relation to another well-established developmental stagespecific keratin, K14, which delineates undifferentiated epidermal basal cells in stratified epithelia [13,26,31], in various epithelia of newborn CD1 wild type mice, including the oral epithelium ( Fig. 1a and b), tongue ( Fig.…”
Section: Resultsmentioning
confidence: 76%
“…Porter et al (2000) described keratin K5 þ and K15 þ cells, in the basal membrane layer, in that they could be a potential stem cell population. Lavker postulated that stem cells would be located at a depth of the rete ridges of the basal layer being protected from the injuries (Webb et al, 2004;Porter et al, 2000;Lavker and Sun, 1983). Webb et al (2004) showed that a α6intþ/K15þ subpopulations were actually located at a depth of the rete ridges, describing these cells as a stem cell population.…”
Section: Discussionmentioning
confidence: 98%
“…The TA cells regenerate the skin by moving upwards and laterally from the stratum basale to other layers during the differentiation process. The TA cells increase their cytoplasmic size, accumulate keratin, and oils providing strength and impermeability to the skin until delamination occurs (Porter et al, 2000) (Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…En effet, sa production augmente dans le cas du carcinome basocellulaire mais elle est supprimée dans les carcinomes épidermoïdes, le psoriasis et dans des 64 conditions hyperproliférantes de l'épiderme (cicatrisation des plaies) (Porter et al, 2000;Waseem et al, 1999), La régulation à la baisse de Kl5 dans les maladies inflammatoires est liée à la préactivation des kératinocytes sous l'effet d'une production accrue de cytokines et de facteurs de croissance tel que transforming growth factor-beta (TGF-p), tumor necrosis factor-alpha (TNF-a) et epidermal growth factor (EGF) (Werner and Munz, 2000). Sous l'effet de cette production, les kératinocytes migrent vers les couches supérieures de l'épiderme pour produire d'autres kératines (Kl, K10, K16, K17) en réponse au signal d'activation (Waseem et al, 1999).…”
Section: Préactivation Des Kératinocytesunclassified